Introducing the Malay song Zapin "Usik- Mengusik" to Minangkabau Teenagers through SMK 2 Padang Panjang School, West Sumatra - Sumbari Putra, Aldi; Enida, Delfi; Supriando, Supriando (Scoring: Journal of Film Music, 2023)
The song Zapin Usik Mengusik is a Malay Pop song in the zapin style created by a figure from Malaysia named Naz. This song was popularized by the Lakon Senario and Haida groups in neighboring Malaysia. This song is very suitable for teenagers who are in love. The rhythm of this song is typical Malay, verse after verse like a rhyme that follows each other. The author is interested in introducing this Malay song to Minang cultured teenagers who of course hear Minang songs more often. The author rearranged this song in the form of a Malay zapin-style ensemble using traditional and modern musical instruments including electric guitar, bass guitar, jimbe drum, string (keyboard), accordion (keyboard), cajon, tambourine, gendang kompang and vocals. This qualitative research is to see the response of Minangkabau cultural teenagers to Malay culture. To obtain this response, this research was supported by lecture methods, demonstrations, training, and evaluation methods. Response indicators are obtained when teenagers in the student category gain knowledge and are able to play and perform the Malay song Zapin Usik Mengusik in a musical ensemble format at SMKN 2 Padangpanjang through the song Zapin Usik Mengusik.